The effectiveness of the Portage program for early intervention in developing the social skills of autistic children (A field study on a sample of students from Bashaer Al-Nour Association in Lattakia) - دلالة ميرنا; صوفي زينا (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of this research is to identify the effectiveness of applying the Portage program for early intervention in developing the social skills of autistic children by reviewing the most important characteristics related to the social skills of this category of children, and then applying a questionnaire before the sample is subjected to the Portage program and six months after they undergo it, the questionnaire included all of the characteristics related to social skills in autistic children. The questionnaire was applied on a sample of 10 autistic children, and the research reached a main conclusion that there were statistically significant differences in the effectiveness of applying the early intervention program (Portage) in alleviating symptoms of poor social skills among autistic children, according to the pre and post measurements.